Analytical evaluation of energy efficiency potential enhancement of heat-generating units by flow variation in the boiler circuit; MATEC Web of Conferences; Vol. 110 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2017) - Artamonov P. A. Pavel (2017, 2017)
Title screen